PELATIHAN PENERAPAN MODEL LATIHAN SEPAK TAKRAW UNTUK PELATIH DI JAKARTA TIMUR - Abdul Gani; Sofyan Hanif; Masnur Ali (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
Abstract This Community Service aims to help trainers understand training models and the application of technology, especially in fostering takraw achievements. Besides that, coaches can also understand the types of variations of exercises for athletes who will be coached by either clubs or students and coaches can practice directly the types of drills to develop the practice of takraw models. The implementation program will be carried out through seminars, workshops and field practice depending on the situation and conditions of Covid 19 at the service location. In the first stage, the coaches/coachers explained the theory of practicing sepak takraw, training methods, training models and how to carry out basic technical drills for special sepak takraw athletes whentraining basic techniques and advanced techniques, then these types of exercises were practiced by the coaches and the application of sports technology in sepak takraw. This community service is carried out in coordination with partners at PSTI DKI Jakarta. The implementation of PKM starts from May – October 2022. It is hoped that from the results of community service carried out by coaches/trainers they can understand the methods of training basic techniques and advanced techniques in the game of takraw, application of technology, so that they can improve their skills to the fullest or reach the peak at the right time. right and they can do coaching, mass takraw, as a result of the trainer training process it is hoped that athletes can compete in achievements when there are events at the national level. Abstrak Pengabdian Masyarakat ini bertujuan untuk membantu para pelatih agar memahami model-model latihan dan penerapan teknologi khususnya pada pembinaan prestasi sepak takraw. Disamping itu juga para pelatih dapat memahami jenis-jenis variasi latihan bagi para atlet yang akan di bina baik klub atau pelajar dan para pelatih dapat melakukan praktek langsung jenis-jenislatihan drill pengembangan model latihansepak takraw. Program pelakasanaan akan dilakukan melalui seminar, workshop dan praktek dilapangan tergantung situasi dan kondisi covid 19 di lokasi pengabdian. Tahap pertamapara pelatih/pembina dijelaskan tentang teori dalam melatih sepak takraw, metode Latihan, model-model latihan dan cara melaksanakan drill teknik dasar padaatlet sepak takraw khusus pada saat melatih teknik dasar dan teknik lanjutan, kemudian jenis-jenis latihan tersebut di praktekan oleh para pelatih dan penerapan teknologi olahraga pada sepak takraw. Pengabdian masyarakat ini dilaksanakan dengan berkoordinasi dengan mitra di PSTI DKI Jakarta. Pelaksanaan PKM dimulai dari bulan Mei – Oktober 2022. Diharapkan dari hasil pengabdian masyarakat yang dilakukan para pembina/ pelatih dapatmemahami metode melatih teknik dasar dan teknik lanjutan dalam permainan sepak takraw, penerapan teknologi, sehingga dapat meningkatkan keterampilan secaramaksimal atau mencapai puncak di waktu yang tepat serta mereka bisa melakukan pembinaaan, pemassalan sepak takraw, akibat dari proses pelatihan pelatih diharapkan para atlet bisa bersaing dalam prestasi ketika ada event di tingkat nasional.